PENGEMBANGAN PENDIDIKAN LIFE SKILL PEREMPUAN BERBASIS LOKAL - Suharnis, Suharnis (Musawa: Journal for Gender Studies, 2017)
Life skill education is education that provides basic provision and proper practice to the community about the values of life needed and useful for the development of people's lives, especially in women. The form or model of life skills development can be seen through the way of learning in developing life skills that is to provide questions/asks that encourage others to do/think. The types of questions asked or the tasks assigned by the teacher or instructor are very influential on the development of people's thinking skills. The questions/tasks are not only to focus on activities, but also to explore or know the potential of each region, so as to trigger analytical, evaluative, and creative thinking and can train in solving problems that occur in self, or in her family.